Antioxidant and vasodilatory activity of commercial beers. (July 2017) - Oliveira Neto, Jerônimo Raimundo; de Oliveira, Thiago Sardinha; Ghedini, Paulo César; Vaz, Boniek Gontijo; Gil, Eric de Souza
Highlights: The antioxidant capacity (AOC) of Beers was investigated. The electrochemical index was compared with traditional spectrophotometric methods. AOC correlations with phenolic composition and vasodilatory effects were evaluated. Abstract: The antioxidant properties of commercial beers were examined by spectrophotometric and electroanalytical methods. Moreover, such properties were correlated with their main phenolic compounds as well as vasodilatory effects. Ale group showed better antioxidant activity and Total Phenols Content (TPC) values than Lager group. The highest electrochemical Index (EI) was observed for LB10 and AB1. Principal Components Analysis (PCA) showed three groups, where group III confirm LB10 and AB1 like the best antioxidant potential. LB10, AB1 and AB6 showed vasodilatory effect of 92 ± 4, 88 ± 3 and 79 ± 3%, respectively. Both the vasodilator effect and the lipid peroxidation inhibition capacity may be associated with the presence of phenolic compounds as caffeic acid, catechin and isoxanthohumol, identified by mass spectrometry. The results showed here expand knowledge about beer, which might be helpful for further research on the health, sensory properties and quality parameter of this beverage worldwide consumed.